2014
DOI: 10.1007/s00198-014-2938-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between non-enzymatic glycation, resorption, and microdamage in human tibial cortices

Abstract: Purpose/Introduction Changes in the quality of bone material contribute significantly to bone fragility. In order to establish a better understanding of the interaction of the different components of bone quality and their influence on bone fragility we investigated the relationship between non-enzymatic glycation, resorption, and microdamage generated in vivo in cortical bone using bone specimens from the same donors. Methods Total fluorescent advanced glycation end-products (AGEs) were measured in 96 human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…fAGEs were indeed increased by ~81% in ribose‐treated specimens compared with vehicles. The AGE levels in vehicles were like those reported in human cortical bone in vivo in two studies but were higher than those reported by another study (Table ). It is difficult to ascertain why the third study reports much lower AGE values as that study also used human female tibias from a similar age range.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…fAGEs were indeed increased by ~81% in ribose‐treated specimens compared with vehicles. The AGE levels in vehicles were like those reported in human cortical bone in vivo in two studies but were higher than those reported by another study (Table ). It is difficult to ascertain why the third study reports much lower AGE values as that study also used human female tibias from a similar age range.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, studies using diabetic animals suggest that increased AGEs are associated with lower bone stiffness and are more susceptible to microcrack propagation compared with non‐diabetic controls, but there is little information regarding crack initiation and propagation due to AGEs in human bone . Further, about 12 studies in human bone focused on studying the effect of non‐enzymatic glycation on cancellous bone mechanical behavior, but only six studies report findings on cortical bone, two of which utilize bovine bone . There is some indication that in diabetes (where AGEs are particularly relevant) cortical bone is the primary bone type affected with a reduced quality .…”
mentioning
confidence: 99%
“…Therefore, the negative spatial correlation between resorption cavities and microdamage in the current study may be a result of more ductile tissue near trabecular surfaces (due to younger local tissue age). However, increased non-enzymatic glycation (a trait associated with increased tissue brittleness [32]) has been shown to impair osteoclastic bone resorption in vitro [40] and is negatively correlated with resorption cavities in cortical bone [41]. If such a negative correlation also exists in cancellous bone it could also explain the negative correlation between microdamage and resorption cavities we observed.…”
Section: 0 Discussionmentioning
confidence: 91%
“…AGEs have been implicated in the deterioration of tissue properties in many different tissues, including bone. [11] AGE crosslinking in collagen has been demonstrated to increase bone fragility [12; 13; 14; 15; 16; 17]. …”
Section: Introductionmentioning
confidence: 99%